Radiographic Imaging and Osteometric Analysis Os Penis in Red Fox (Vulpes vulpes) - Kanmaz, Yesım Aslan; Baygeldı, Saıme Betül (My University, 2024)
The aim of this study was to determine the macroscopic features of the os penis of the Red Fox (Vulpes vulpes), as well as radiographic images and morphometric measurements using a digital electronic caliper. In this study, 4 adult male red fox os penises, which were previously brought dead from nature by students and whose skeletons were exhibited in our anatomy museum, were used. Macroscopic and morphometric measurements were taken and anatomical structures were analysed by radiographic imaging. Os penis is thicker at the proximal end and tapers towards the distal end, terminating in a cartilaginous tip. There are three margins, one dorsal and two ventrolateral to the sulcus urethiralis. The dorsal edge forms a crista on the median of the bone, extending from proximal to distal. The crista becomes shallow at the distal 1/3 of the bone and disappears completely at the cartilaginous end. Sulcus urethralis is found on the ventral side Os penis of the Red Fox measured as, length of the os penis 56.70mm, Distal diameter 2.96mm, Proximal diameter 3.85mm, length of the sulcus urethralis 35.13mm, width of sulcus urethralis 2.95mm, length of the fibrous cartilaginous tissue 5.70, width of the fibrous cartilaginous tissue 1.77mm. As a result, it has been observed that the os penis of the red fox, which is a part of wildlife, is similar to the other members of the team, the dogs, and radiographic images have been combined with new techniques and a literary contribution has been made. Wild animal anatomy has been supported by more detailed examination of these species. It is thought that the data obtained in the study can be used in future morphometric, zoo-archaeological and taxonomic studies.
Keywords: Red fox; Osteometric analysis; os penis; radiographic ımaging